Behavioral Intention in Forensic Accounting Services - Liyana Adila Azman, Nur; Vaicondam, Yamunah (International Journal of Psychosocial Rehabilitation, 2020)
Forensic Accounting Services (FAS) have played an important role in the prevention and detection of fraud, and the demand for FAS is growing due to the heightened sensitivity to fraud. However, the primary worry in this paper is that FAS has become one of the least used tools in the prevention and detection of fraud, and the increasing number of frauds from three sectors—manufacturing, financial services, and communication industries—may indicate that FAS has not been effectively used. The main objective is to study the behavioral intention of using FAS. The two main theories and the elements used in this study are Theory Planned of Behavior (TPB) and Protection Motivation Theory (PMT), with an additional variable of organizational norms. This study is expected to generate the best model on the development of behavioral intention in FAS in fraud prevention and detection by individuals in listed firms. This study may significantly contribute to the consideration of strengthening the usage of FAS by listed firms and institutions for the prevention and detection of fraud in Malaysia, and institutions in Malaysia may consider implementing a specialized course on forensic accounting to meet the increasing demand in the Malaysian market for FAS.